Seasonal measurements of OH, NOx, and J(O1D) at Mace Head, Ireland. Issue 8 (28th April 2013) - Berresheim, H.; McGrath, J.; Adam, M.; Mauldin, R.L.; Bohn, B.; Rohrer, F.
Abstract : [1] Measurements of atmospheric OH concentrations were conducted between August 2010 and July 2011 at Mace Head showing maximum daytime values of 0.21 (±0.25) × 10 6  cm −3 in winter and 2.26 (±1.37) × 10 6  cm −3 in summer. Plots of OH versus ozone photolysis frequency, J(O 1 D), exhibited strong linear correlations with slopes of 1.06 (±0.05) × 10 11  cm −3  s (R = 0.75) in clean marine air and 1.31 (±0.04) × 10 11  cm −3  s (R = 0.79) in mixed marine/continental air. Surprisingly, no significant difference in the former correlation was found between low and high tide periods. NO and NO2 levels in air from the marine sector (190–300°) were typically below the detection limit (30 pptv and <200 pptv, respectively). In the land sector, NO mixing ratios <50 pptv dominated most of the time, suggesting that the atmospheric oxidation efficiency in this region is predominantly characterized by primary OH sources in a low NO x environment. Key Points: First long‐term measurements of OH in mid‐latitude marine air are presented OH‐J(O1D) correlations are determined for different NOx regimes OH variance analysis is presented for a 2‐year period